2021
DOI: 10.3390/ijerph182312771
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Healthcare Students’ Experiences of Racial Bias: A Narrative Review of the Role of Implicit Bias and Potential Interventions in Educational Settings

Abstract: Implicit racial bias is a persistent and pervasive challenge within healthcare education and training settings. A recent systematic review reported that 84% of included studies (31 out of 37) showed evidence of slight to strong pro-white or light skin tone bias amongst healthcare students and professionals. However, there remains a need to improve understanding about its impact on healthcare students and how they can be better supported. This narrative review provides an overview of current evidence regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…Previous studies in medical schools in England have found that ethnic minority healthcare students have higher stress compared to their white peers and qualitative interviews with trainee doctors showed strained relationships with seniors due to a perceived bias during work-based assessments and the psychological impact of stereotypes [5,6]. This study describes the experience of BAME medical students in Wales, combining the impact of a less ethnically diverse local population than in the UK in general with being on a graduate-entry course, which tends to have signi cantly lower proportions of BAME entrants compared to undergraduate medical courses [7,8].…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies in medical schools in England have found that ethnic minority healthcare students have higher stress compared to their white peers and qualitative interviews with trainee doctors showed strained relationships with seniors due to a perceived bias during work-based assessments and the psychological impact of stereotypes [5,6]. This study describes the experience of BAME medical students in Wales, combining the impact of a less ethnically diverse local population than in the UK in general with being on a graduate-entry course, which tends to have signi cantly lower proportions of BAME entrants compared to undergraduate medical courses [7,8].…”
Section: Introductionmentioning
confidence: 93%
“…34 Ground rules, such as respect and confidentiality, create a nonthreatening space to foster vulnerability and learning. [43][44][45] This atmosphere enables sensitive discussions to take place among nurses and colleagues and encourages growth. Implicit bias is part of being human; however, overcoming one's misconceptions is necessary to prevent harmful clinical decisions.…”
Section: Choice Of Languagementioning
confidence: 99%
“…Systematic racist beliefs spread through hierarchy, power, and media, make it more likely that White nursing students will think or act in a biased manner (Roberts & Rizzo, 2021). It was found that White students exposed to demonstrations of racial bias expressed racial bias themselves (Joseph et al, 2021). An additional concern is that implicit bias plays a role in recruiting and retaining nurses of color (Joseph et al, 2021).…”
Section: Integration Of Jedi Principlesmentioning
confidence: 99%
“…It was found that White students exposed to demonstrations of racial bias expressed racial bias themselves (Joseph et al, 2021). An additional concern is that implicit bias plays a role in recruiting and retaining nurses of color (Joseph et al, 2021). Being aware of the role that these biases play will lead to more optimal nursing care.…”
Section: Integration Of Jedi Principlesmentioning
confidence: 99%